Study the effect of thickness and reflectivity on (n-ZnSe / p-MASnI3 / p-CuSCN) solar cell properties using SCAPS-1D - Tariq A. Mohammed; Ayed N. Saleh (Tikrit Journal of Pure Science, 2019)
The effect of the absorption layer (MASnI3) within the range (200nm-900nm) was studied with the thickness of each layer HTM and ETM (10nm) for each. After completion of the study we found that the best thickness of the absorption plate is at (400nm), note that the cells used in the program is not perfect it contain defects, to be closer to the practical reality, after completing this study In the framework of this study was added a filter mirrors (95% mirro) from the library of the program (Scaps) and that the studied solar cells (n-ZnSe / p-MASnI3 / p-CuSCN) Reflectivity (R) ranged between 0.11-0.99 and the best reflective range at 0.99 was (η) 20.98 filler (FF) 68.55% short circuit current (Jsc) 34.040 mA/cm2 and volt circuit (Voc) 0.894 V. The default illumination spectrum has been set to the AM1.5 global standard.